Investigating Homophily in Online Social Networks - Bisgin, Halil; Agarwal, Nitin; Xu, Xiaowei (2010 IEEE/WIC/ACM International Conference on Web Intelligence and Intelligent Agent Technology, 2010)
Similarity breeds connections, the principle of homophily, has been well studied in existing sociology literature. %Several studies have observed this phenomena by conducting surveys on human subjects. These studies have concluded that new ties are formed between similar individuals. This phenomenon has been used to explain several socio-psychological concepts such as segregation, community development, social mobility, etc. However, due to the nature of these studies and limitations because of involvement of human subjects, conclusions from these studies are not easily extensible in online social media. %Social media, which is becoming the infinite space for interactions, has exceeded all the expectations in terms of growth, for reasons beyond human mind. New ties are formed in social media just like the way they emerge in real-world. However, given the differences between real-world and online social media, do the same factors that govern the construction of new ties in real-world also govern the construction of new ties in social media? In other words, does homophily exist in social media? In this article, we study this extremely significant question. We propose a systematic approach by studying two online social media sites, BlogCatalog and Last.fm and report our findings along with some interesting observations.